Analytical Approach to the Implementation of Mortgage Law on Flat Owned by Foreigner in Indonesia and Singapore - David Tan (Journal of Judicial Review, 2017)
Looking at the effects of globalization, the amount of expatriates coming to Indonesia and Singapore is constantly increasing. They come as a foreigner to do business and stay within a period of time. The scarcity of land area and certain national interest against land, are factors pushing the development of flats and strata living area (strata title). This type of dwelling is commonly the choice preferred by foreigner to live on. The flat ownership criteria and its rights to serve as a security interest for loan, especially for foreigner who owns it is then the problems arising out of it. This research is carried out to find out the process of owning a flat and its charge as security interest, such as encumbrance right/mortgage, especially by foreigner, both in Indonesia and Singapore. The prerequisite, process, advantages and disadvantages of methods used by the two countries. This research is using the normative juridical method of analyzing the laws of Indonesia and Singapore. Sources of data used are in forms of primary legal materials, secondary legal materials and tertiary legal materials. Data collection technique is done through the method of literature study (library research). After all of the data are collected, the data are processed and analyzed. The qualitative analysis is used with the intentions to classify aspects of data studied. Furthermore, it is then concluded that the research associated with this is then described descriptively. Based on the results of this study and research showed that there are some similarities and differences regarding the process of owning a flat and its charge as security interest, such as encumbrance right/mortgage by foreigner in Indonesia and Singapore. This similarities and differences, especially in the law system implemented by both countries also caused several advantages and disadvantages regarding it.